Ranking of Murrah buffaloes by multi-trait criteria of selection - GANDHI, R S (The Indian Journal of Animal Sciences, 2014)
First lactation 316 records were used to rank Murrah buffaloes using multi-trait criteria of selection like optimum selection index. standardised principal components scores (6) and indices based on principal components (2). The ranking of buffaloes from the aforesaid criteria was cpmpared with first lactation 305 - day or less milk yield. The genetic and phenotypic variances and covariances among 7 first lactation traits, viz. AFC, FLMY. FLL. FCI. MY/FLL. MY/fCI and MY/ASC, were used to construct selection indices and to derive standardized principal components scores (PCSs). Out of 40 selection indices. an index having AFC, FLMY, FLL, FCI and MY/ASC was considered to be optimum giving expected genetic gain of Rs 288.75 and accuracy of prediction of 75.9%. Out of 14 principal components (PCs) constructed both from genetic and phenotypic variances and covariances, first 3 PCs from each set explained more than 99% of total variation of the population and the 6 PCSs derived from these PCs were used as criteria of selection. Two more indices based on variance explained by principal components derived from genetic (I1) and phenotypic (I2) variances/covariances were constructed. The rank correlation of FLMY with optimum selection index (I3) was moderate and highly signiticant (0.4889). On the contrary, its coefficients of correlation with the indices derived from principal components (I1 and I2) were very high’ (>0.9). Similarly, the rank correlations of FLMY with synthetic variates derived from first principal component from both genetic as well as phenotypic variances and covariances were near to unity. The rank correlations of optimum selection index with indices derived from principal components were 0.5404 (I1) and 0.4109 (I2) indicating that ranking of buffaloes from optimum selection index was significantly different from indices nerived fromprincipal components.